Gambaran Penyakit Periodontal pada Pasien Diabetes Melitus di Puskesmas Bara - Barayya - Zahrawi Astrie Ahkam; Hasrini Hasrini; Amirah Maritsa; Arfiah Jauharuddin; Dewi Sartika (Jurnal Siti Rufaidah, 2023)
Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia that occurs due to insulin secretion, insulin action or both. This disease is a disease that is widely suffered by the community and continues to grow in Indonesia. Periodontal disease is a dental and oral health problem that has a fairly high prevalence in the community where periodontal disease occurs in all age groups in Indonesia. The purpose of this study was to determine periodontal disease in patients with diabetes mellitus at the Bara-Barayya Health Center. This type of research is a descriptive study with a sample of 60 people taken using the total sampling technique. Samples were examined using the gingival index and CPITN index assessment criteria. The results showed that those who experienced periodontitis with a score of 4 were the highest, namely 18 people (44%), and subjects who experienced a score of 2 were the fewest, namely 8 people (19.5%). While those who experienced gingivitis were the highest, namely severe gingivitis, as many as 10 people (52.6%) and the fewest were those who experienced mild gingivitis, as many as 5 people (26.3%). Based on the results of this study, it can be concluded that the most common periodontal disease found in diabetes mellitus patients at the Bara-Barayya Health Center is periodontitis, namely 41 people (68.3%) and the least is gingivitis, namely 19 people (31.7%).